1999
DOI: 10.1093/hmg/8.12.2239
|View full text |Cite
|
Sign up to set email alerts
|

Detection of an Appropriate Kinase Activity in Branchial Arches I and II That Coincides with Peak Expression of the Treacher Collins Syndrome Gene Product, Treacle

Abstract: Treacher Collins syndrome (TCS) is an autosomal dominant craniofacial disorder involving the mid and lower face and, in particular, the tissues affected arise solely from embryonic branchial arches I and II. TCOF1, the gene involved in TCS, has been cloned and although the function of the encoded protein, treacle, has not yet been established, it exhibits peak expression in the branchial arches. Treacle contains a series of repeating units of acidic and basic residues, which are predicted to contain putative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 18 publications
3
17
0
2
Order By: Relevance
“…Previous experiments have shown that the association between NBS1 and many of its interactors, such as MDC1 and CtIP, is mediated by NBS1's FHA domain, which binds to protein motifs phosphorylated by CK2 (14-16). TCOF1 harbors 10 highly repetitive regions, known as treacle repeats, containing conserved CK2 sites and is a known CK2 substrate (17,18). Consistent with these observations, we identified a CK2 subunit CSNK2B as part of a TCOF1 complex (Fig.…”
Section: Nbs1 Localization To Nucleoli After Ir Is Dependent On Caseisupporting
confidence: 85%
“…Previous experiments have shown that the association between NBS1 and many of its interactors, such as MDC1 and CtIP, is mediated by NBS1's FHA domain, which binds to protein motifs phosphorylated by CK2 (14-16). TCOF1 harbors 10 highly repetitive regions, known as treacle repeats, containing conserved CK2 sites and is a known CK2 substrate (17,18). Consistent with these observations, we identified a CK2 subunit CSNK2B as part of a TCOF1 complex (Fig.…”
Section: Nbs1 Localization To Nucleoli After Ir Is Dependent On Caseisupporting
confidence: 85%
“…They share a characteristic sequence rich in serines and acidic amino acids forming phosphorylation sites for CK2 [100] close to a stretch of basic amino acids. Nucleolin, Srp40p, Nopp140, and TCOF1 are nucleolar proteins and known substrates for CK2 [101][102][103][104]. Nucleolin and Nopp140 can be highly phosphorylated, and the phosphorylation process of Nopp140 by CK2 occurs in a cooperative manner with phospho-serines produced by CK2, creating new CK2 phosphorylation sites [103].…”
Section: Protein Pyrophosphorylationmentioning
confidence: 99%
“…A kinase activity in avian branchial arches, thought to be CK2, phosphorylates the protein treacle, the product of the TCOF1 gene that is mutated in Treacher Collins syndrome (TCS). TCS is a craniofacial disorder that affects the embryonic branchial arches leading to face abnormalities [ 87 ].…”
Section: Ck2 In Pharyngeal Arch Derivativesmentioning
confidence: 99%